Pengaruh Metode Perkuliahan Daring Dan Minat Belajar Terhadap Tingkat Pemahaman Akuntansi Dengan Kecerdasan Emosional Sebagai Variabel Pemoderasi Selama Pandemi Covid-19 - Ni Made Fanny Sukma Rahayu; I Putu Deddy Samtika Putra (UNHI Press, 2023)
During the Covid-19 pandemic, the pattern of people's lives changed. One aspect that has been affected by COVID-19 is education. In the world of conventional education, the teaching and learning process is usually carried out face to face, but due to the pandemic, the entire learning process is carried out online. In the current observations, the author wants to reveal the effect of online lecture methods and interest in learning on the level of understanding of accounting with emotional intelligence as a moderating variable during the Covid-19 pandemic. This study made all accounting students at the Hindu University of Indonesia, totaling 700 students, as the study population, in which the total sample was 88 people who were analyzed using the (MRA) technique. The results of this study indicate that the level of understanding of accounting can be higher if the lecture method is online, the interest in learning is increased. Emotional intelligence is not able to strengthen the effect of online lecture methods on the level of understanding of accounting.